Water Warriors Living Lab: Towards an integrated “Heartware - Hardware – Software” Approach to Water Management - Zeeda Fatimah Mohamad; Siti Norasiah Abd Kadir; Affan Nasaruddin; Fathiah Mohamed Zuki; Hazreena Hussein; Nor Aishah Abdullah; Abdul Halim Sulaiman; Sharifah Noor Nazim Syed Yahya; Mohammad Zainuddin Borhan; Mohd Ramzi Mohd Ruslan; Nordiana Mohd Isa (Universitas Diponegoro, 2022)
This paper presents the experience of the Water Warriors Living Lab, a bottom-up sustainable campus action research initiative in applying the integrated ‘Heartware - Hardware – Software’ approach for water management at the University of Malaya since the year 2013. It advances the proposition that a heartware approach is needed to enhance campus sustainability efforts, in addition to the more strategic hardware and software approaches. The paper describes how the Water Warrior’s experience in applying the heartware approach has been a strengthening factor in resolving water conservation issues at the university (specifically in lake management), and discusses important lessons learned to date. Our theoretical and empirical insights can hopefully provide renewed appreciation on how local, organic and humanistic factors can be essential ingredients for the long term ‘sustainability’ of campus sustainability efforts.Keyword: Campus sustainability, living lab, water management, heartware, bottom-up